Intraabdominal pressure in acute pancreatitis - Lizárraga Mendoza, Karlo (2009)
Introduction: Early assessment of acute pancreatitis severity is particularly important for its adequate treatment. Objective: To establish the usefulness of non-invasive intra-abdominal pressure (IAP) measurement for such assessment. Material and method: IAP was measured using the Kron technique (bladder pressure), in 78 patients with acute pancreatitis at 24, 48, and 72 hours after the onset of the disease, mean values were obtained, and they were compared for both mild and severe forms of the disease, according to APACHE II and Ranson scores; and the Tomographic Index was also used. A correlation between these parameters was also assessed. Results: In mild disease cases, mean values for the aforementioned parameters at 24, 48, and 72 hours were 5.85 ± 1.08; 7.57 ± 2.36, and 7.95 ± 1.21 mm Hg; and for the severe form, mean values were 10.39 ± 1.67; 11.91 ± 3.07, and 15.39 ± 2.21 mm Hg, respectively (p<0.01), at the same time points. IAP values showed a linear positive correlation with APACHE II, Ranson and Tomographic Index scores (p<0.01). The IAP was always ≥ 7 Hg mm at 24 hours and ≥ 13 Hg mm at 72 hours in severe pancreatitis. Conclusions: IAP measurement, using an easy, cheat and accessible method, may be useful for performing an early assessment of acute pancreatitis severity, especially when other scores may not be established. Future research will set up specific values, but those ≥ 7 mm Hg at 24 hours or ≥ 13 mm Hg at 72 hours could be used as danger parameters.